The Effect of Role Play Method with Pancasila Student Profile Dimension on Speaking Ability in Early Childhood - Delsiana Inna; Putu Indah Lestari; Ni Made Ayu Suryaningsih (Sean Institute, 2025)
Speaking ability is an important aspect in children's language development. Speaking ability includes oral pronunciation of sounds, pronunciation, grammar, vocabulary, fluency, and understanding. This study aims to determine the effect of the role-playing method with the dimensions of the Pancasila student profile on speaking ability in early childhood. This research includes experimental research, namely Quasi Experimental Design and the design used is Non-Equivalent Control Group Design. Data collection using observation method. The subjects of this study were Group B children of Widya Kumara Dalung Kindergarten consisting of control class and experimental class. Data analysis results show t (count) = 3.440while at a significant level of 5% with dk = 94 obtained t (table) value of 1.661.So it can be seen that t (count) > t (table)is 3.440 > 1.661which means Ho is rejected and Ha is accepted. Based on the results of the t-test calculation, it shows that there is a significant effect of applying the role-playing method with the dimensions of the Pancasila student profile on speaking skills in early childhood.